Adolescent Reproductive Health Service in Accessing HIV and AIDS Information: Layanan PKPR dalam Akses Informasi HIV dan AIDS - Kurniawati, Herlin Fitriani; Kurniawati, Herlin Fitriana (Universitas Muhammadiyah Sidoarjo, 2022)
Adolescent reproductive health problems are very complex, one of them is HIV and AIDS. Adolescent Reproductive Health Service (PKPR) in Public Health Center the aims to increase adolescent knowledge about adolescent healthy behavior including reproductive health. The research aimed to identify utilization of Adolescent Reproductive Health Service in acces HIV and AIDS information in Kulon Progo. The research used a quantitative design, The population in the research is senior high school students. The sampling technique was simple random sampling with a sample of 125 respondents. The data collection instrument in this quantitative study was a questionnaire using google form, the data was processed using the steps of editing, coding, tabulating and analysis. The results showed that 73% of respondents had good knowledge, 60% of respondents had poor knowledge of PKPR Puskesmas and 56% of respondents used PKPR services for adolescents. The provision of adolescent reproductive health services is in accordance with the needs of adolescents and it is necessary to increase the promotion of adolescent reproductive health services so that they are more familiar with and can access services.